2013
DOI: 10.7860/jcdr/2013/4804.2727
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Conduction Studies in the Upper Limb in the Malwa Region-Normative Data

Abstract: Objective: To establish the normal electrophysiological data for the median and the ulnar nerves in normal healthy adults in the Malwa region of Punjab, India. Methods:Nerve conduction studies were performed prospectively in the upper limbs of 100 carefully screened, healthy individuals of either sex, who were between the ages of 20 and 60 years, by using a standardized technique. Results:Motor studies: The median distal latency (DL) in men was 3.4 (0.2) ms, the amplitude (CMAPA) was 10.80 (2.8) mV, the conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 7 publications
5
25
2
Order By: Relevance
“…Garg R et al [14] in their study of upper limb in malwa region had found that sensory nerve action potential ISSN-2321-127X…”
Section: Discussionmentioning
confidence: 99%
“…Garg R et al [14] in their study of upper limb in malwa region had found that sensory nerve action potential ISSN-2321-127X…”
Section: Discussionmentioning
confidence: 99%
“…Males have significantly lower SNAP amplitudes of median and ulnar nerves, which match Stetson et al's 11 observations in the same nerves, 11, this difference may be explained by thicker subcutaneous tissue (finger circumference) among males, which result in a greater distance between the surface electrode and the digital nerves, hence causing diminished SNAP amplitudes. 11,19 Sensory peak latencies (SPL) were also measured along with SDLs and as shown in Table 3, SPLs are more sensitive to gender comparisons. SDLs were employed in this paper because they are a good indication of the fastest nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,21 Most of our values were similar to four other similar published studies. 2,3,5,8,13,21,22,23 However, there were some differences, which could be attributed to different NCS techniques, machine settings, and demographic characteristics. A notable dissimilarity was in the CMAP and the SNAP amplitudes because some studies used peak-to-peak measurement and others used baseline-to-negative peak measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations